(untitled) (Actualizaciones en Sida e Infectología, 2019)
Background: Antimicrobial treatment for febrile neutropenic (FN) patients has become a challenge due to the growing emergence of multidrug-resistant microorganisms (MDR-MO). The objective of this study was to analyze the characteristics of these population and the incidence of MDR-MO. Methods & Materials: Retrospective, observational and descriptive study from June 2015 to August 2017 in FN adults hospitalized at a public hospital in Buenos Aires city, Argentina. Demographic, clinical and microbiological characteristics were analyzed. We included the following MDR-MO: extended spectrum beta-lactamase (ESBL) and carbapenemase-producing Enterobacteriaceae (CPE), Acinetobacter baumannii complex, vancomycin resistant Enterococcus (VRE) and Stenotrophomonas maltophilia. Results: Thirty-two patients were included; 56% were women, with 84% haematological diseases. Colonization by CPE or VRE was observed in a 59% of the patients. There were 148 infectious episodes. Of them 41% had microbiological documentation. MDR-MO were responsible for 25% of the episodes and the most frequent were carbapenemase-producing Klebsiella pneumoniae and ESBL producing Enterobacteriaceae. MDR-MO were isolated mainly from bacteremia and urinary infections, patients had acute leukemia in a 67% and colonization CPKP or VRE in 80%. Inadequate treatment for MDR-MO was observed in 63% of the cases and 12% for susceptible microorganisms (p<0,01). The mortality was 53% for MDR-MO and 27% for susceptible microorganisms (p=ns). Conclusion: MDR-MO infections were frequent with predominance of bacteremia especially CPE and ESBL producing Enterobacteriaceae. According to these results MDR-MO should be taken into account for the empiric antimicrobial treatment in febrile neutropenic patients.